Flexural performance of hollow-core partially-encased composite beams. (January 2022) - Ye, Yanxia; Yao, Yifan; Liao, Hanyu; Xin, Li; Liu, Yuan
Abstract: To conserve steel resources and reduce the weight of structural beams while ensuring sufficient load-bearing capacity and stiffness, a novel hollow-core partially-encased composite beam (HPEC) is proposed in this article. In this new composite beam, the foam formwork lies within the steel flanges, and high-strength cementitious grout is encased in the remaining space. Flexural experiments on four HPEC beams and two comparison specimens were conducted while considering the grouting strength, thickness, and shear stud arrangement in the beams. Typical flexural failure modes and crack patterns were observed, and the high-strength cementitious grout partially encased within the steel flanges improved the stiffness and flexural capacity. The welded studs delayed concrete cracking and improved the integrity of the composite beams. The flexural capacity of the HPEC beam was similar to that of the control specimen. However, the dead weight of the beam was reduced significantly, to only 43.33% of the control specimen. According to the elastic and plastic theories, the flexural capacities at yield load and peak load, respectively, were calculated; the computed results were consistent with the experimental findings, thus confirming that the analytical methods described herein can be applied to accurately predict flexural strength. Highlights: A novel partially encased composite beam with light weight, named HPEC beam, was proposed. Flexural experiments on HPEC beams were conducted considering cementitious grout strength, thickness and shear stud arrangement. A calculation method for the bending capacity of HPEC beams in the yield state and the limit state was proposed.